2022
DOI: 10.3390/pharmaceutics14051012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of BMSC-Derived EVs on Bone Metabolism

Abstract: Extracellular vesicles (EVs) are small membrane vesicles that can be secreted by most cells. EVs can be released into the extracellular environment through exocytosis, transporting endogenous cargo (proteins, lipids, RNAs, etc.) to target cells and thereby triggering the release of these biomolecules and participating in various physiological and pathological processes. Among them, EVs derived from bone marrow mesenchymal stem cells (BMSC-EVs) have similar therapeutic effects to BMSCs, including repairing dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 179 publications
0
26
0
Order By: Relevance
“…Cumulative studies have shown that MSC-EVs can influence downstream signaling cascades by directly translocating their internal cargoes, which in turn regulate bone formation, bone resorption, bone angiogenesis, and immune activity in OP [ 75 , 76 ] (as shown in Figure 2 ). There are many endogenous molecules encapsulated within MSC-EVs.…”
Section: Mechanisms Of Msc-evs In Opmentioning
confidence: 99%
“…Cumulative studies have shown that MSC-EVs can influence downstream signaling cascades by directly translocating their internal cargoes, which in turn regulate bone formation, bone resorption, bone angiogenesis, and immune activity in OP [ 75 , 76 ] (as shown in Figure 2 ). There are many endogenous molecules encapsulated within MSC-EVs.…”
Section: Mechanisms Of Msc-evs In Opmentioning
confidence: 99%
“…Among the many cytokines secreted by MSCs, extracellular vesicles (EVs) are nano-phospholipid bilayer vesicles that can be secreted by almost all cells and are formed by “budding” directly from the plasma membrane. According to their diameter, composition, and origin, EVs can be divided into exosomes (Exos), microvesicles, and apoptotic bodies [ 23 ]. Among them, Exos are the most attractive category of EVs.…”
Section: Introductionmentioning
confidence: 99%
“…Under physiological conditions, osteoclasts and osteoblasts play a role in maintaining bone resorption and formation in dynamic balance [ 1 ]. Bone marrow mesenchymal stem cells (BMSCs) are important precursor cells of the osteoblast line [ 2 ]. Under appropriate conditions, BMSCs can differentiate into mesenchymal-derived cell types, such as chondrocytes, osteoblasts, and adipocytes, which play a crucial role in bone remodeling [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Osteoclasts derived from bone marrow-derived macrophages (BMMs) clear old or damaged bone under the trigger of osteocytes while releasing growth factors from the bone matrix, thus inducing BMSCs recruitment and migration to the repair area, resulting in BMSCs differentiation into osteoblasts and formation of new bone at specific sites [ 4 , 5 ]. However, under the pathological conditions of estrogen deficiency, abnormal mechanical stress, and drug side effects, the homeostasis of bone formation and bone resorption is disrupted, leading to osteoporosis, fracture, nonunion, or osteonecrosis of the femoral head [ 2 ]. Therefore, the regulation of bone formation and bone resorption is the basic strategy for preventing and treating bone metabolism-related diseases, in which osteoclasts and osteoblasts play a crucial role.…”
Section: Introductionmentioning
confidence: 99%